Eugenics Actions in the History of Education: The Impact of Censorship Practices Applied in the Pedagogical Academy of Heraklion, (Crete, Greece) during the April Dictatorship (1967-1974) - Kounalakis, Manolis (Language, Literature and Education: Research Updates Vol. 5, 2025)
This chapter examines censorship forms, overt, latent and productive, implemented in the pedagogical training received by the students (teacher candidates) of the Pedagogical Academy of Heraklion (P.A.H.) (Crete, Greece) during the period of the April dictatorship (1967-1974). These specific forms of imposed censorship are examined to the dynamics they can develop in terms of strengthening eugenic actions or eugenic-type of actions within the context of an authoritarian regime. In the introduction of the chapter, a brief reference is made to the historical context of the period we are examining. The ideological principles of the dictatorship of that period are briefly mentioned, as well as the main changes that took place in the field of education and specifically teacher training. The literature overview of the chapter refers to the concept of eugenics and its basic characteristics, as well as to the themes that the history of education has examined around this concept. This is followed by an explanation of the concept of censorship and the individual forms, overt, covert and productive, that it can acquire. The review concludes with a reference to the main censorship actions of the dictatorial regime under consideration in the period under research.The research was based on the archival material of the Academy, specifically the documents relating to its lending library. The historical interpretive methodology of 'history from below' was followed. The results of the research reveal many acts of censorship, overt or latent, concerning the formation of the institution's lending library towards a eugenic type pedagogy. The findings are consistent with the general idea of the intense censorship activity of the dictators in the period 1967-1972, but highlight similar results for the period 1972-1974, for which relevant research had shown that the phenomenon of censorship was clearly less visible.